2011
DOI: 10.1038/aps.2011.33
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific alterations in expression and function of P-glycoprotein in streptozotocin-induced diabetic rats

Abstract: Aim: To investigate the changes of expression and function of P-glycoprotein (P-GP) in cerebral cortex, hippocampus, liver, intestinal mucosa and kidney of streptozocin-induced diabetic rats. Methods: Diabetic rats were prepared via a single dose of streptozocin (65 mg/kg, ip). Abcb1/P-GP mRNA and protein expression levels in tissues were evaluated using quantitative real time polymerase chain reaction (QRT-PCR) analysis and Western blot, respectively. P-GP function was investigated via measuring tissue-to-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 54 publications
2
35
0
Order By: Relevance
“…The mechanism inducing Oatp2 expression was not reported. In the present study, we reported that DM rats showed a trend toward increasing hepatic Oatp2 levels, which was identical with the findings in type 1 diabetic rats induced by STZ [21] . We also noted that alterations of Cyp3a1, Bcrp and Mrp2 in the liver and intestines induced by diabetes were different.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The mechanism inducing Oatp2 expression was not reported. In the present study, we reported that DM rats showed a trend toward increasing hepatic Oatp2 levels, which was identical with the findings in type 1 diabetic rats induced by STZ [21] . We also noted that alterations of Cyp3a1, Bcrp and Mrp2 in the liver and intestines induced by diabetes were different.…”
Section: Discussionsupporting
confidence: 91%
“…We also noted that alterations of Cyp3a1, Bcrp and Mrp2 in the liver and intestines induced by diabetes were different. Our previous studies showed that alterations in activity or expressions of Cyp3a, Bcrp, Mrp2, and Oatp2 in diabetic rats were dependent on tissues and genes [19,21,45,46] . However, the real mechanisms resulting in the differential alterations were not clear and require additional investigation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One of the major barriers limiting oral drug delivery is the active efflux of drugs from the enterocytes back into the intestinal lumen by P-glycoprotein (P-gp). P-gp is an ATPbinding cassette protein that is responsible for secreting drugs and xenobiotics out of the cell [4] . P-gp is a plasma membranebound drug efflux protein that is expressed on several barrier epithelia, including the intestine, renal epithelial cells and brain capillary endothelial cells [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical reports have underlined the effect of changes in the functional activity of P-gp on the bioavailability and disposition of therapeutic agents [3] . Previous reports have indicated that the expression and function of P-gp are dysregulated under pathophysiological situations such as diabetes mellitus [4,5] , chronic renal failure [6] and inflammation [7] . It is becoming increasingly clear that nitric oxide and its related nitrogen species (NOx) [8] are crucial regulatory mediators of the function and expression of P-gp and other transporters under pathophysiological conditions [8][9][10][11][12][13][14] .…”
mentioning
confidence: 99%